Fintech and banks as complements in microentrepreneurship - Adbi, Arzi; Natarajan, Siddharth (Strategic Entrepreneurship Journal, 2023)
Abstract Research Summary This article studies fintech targeted to the base of the pyramid and its role in encouraging savings for microenterprises. We argue that the impact of fintech adoption on savings for microenterprises by the poor and by women is moderated by their access to banks—specifically, that fintech is more impactful with bank accounts, and this complementarity between fintech and banks is amplified for poor women. We develop hypotheses in the context of mobile money, a popular fintech across the developing world. Our arguments are supported by a sample of 81,345 individuals across 74 low‐ and middle‐income countries. Overall, the paper suggests that, although fintech can be a promising tool for the poor, it is equally important to improve inclusivity in formal banking institutions. Managerial Summary We offer an alternative to the popular narrative that fintech replaces the need for formal banks. In an analysis of 74 low‐ and middle‐income countries, we find that fintech is more useful in encouraging marginalized individuals to save for microenterprises when it is complemented by banks. Our finding of complementarity between fintech and banks, especially for poor women, suggests the need to rethink the notion that fintech is a substitute for banks. We suggest caution in drawing definitive conclusions about the unconditional positive impact of fintech. We recommend that policymakers continue driving financial inclusion with formal banking. Strategic entrepreneurs seeking to tackle grand societal challenges can utilize digital technology to capitalize on the strengths of established institutions.